The plio-pleistocene history of explosive volcanic activity in north Pacific Island arcs and possible links to regional and global climate change. - Prueher, Libby M. (1999)
Deep-sea sediment recovered by Ocean Drilling Project (ODP) Leg 145 contain the best record yet of explosive volcanic activity over a wide geographical region as well as a record of an intensification of Northern Hemisphere glaciation that occurred at 2.65 Ma. Comparison of this ash record with other ODP sites and with terrestrial records demonstrates the reliability of the ash layer stratigraphy and that this ash record is appropriate to use in an investigation of the effects of explosive, silicic, volcanism on climate. The glacial intensification is recorded in the sediment as an abrupt increase in terrigenous clastic sediment and ice-rafted debris (IRD). The number and thickness of volcanic ash layers increases abruptly in the sediment at the same time. Magnetic susceptibility records show that the climate change occurred rapidly, within 1000--2000 years, too quickly to be a response to tectonic or orbital forcing. The rapid, synchronous, basin-wide climate change suggests that the climate forcing mechanism operated over decades to millennia and was hemispherical in extent. The synchronous increase in volcanism suggests that explosive eruptions may have been the trigger of the glacial onset. Ash layers in marine sediment are often the best preserved record of the explosive history of an arc, because deep-sea sediments are less susceptible to erosion. Volcanic ash layers in deep-sea sediments of the northern Pacific Ocean provide a record of the episodic explosive volcanism in the Kamchatka and Aleutian volcanic arcs, including a major episode that began about 2.65 Ma at both arcs. Mass-accumulation rates (MAR) of volcanic glass and IRD were calculated as a way to determine the stratigraphic relationship between the ash and the IRD. Volcanic glass is used as a proxy for explosive volcanic eruptions and IRD is used as a proxy for glaciation. MAR of both the glass and IRD show a five- to ten-fold increase at 2.65 Ma, with the flux of the glass increasing just prior to the flux of the IRD, again suggesting that ...